2009
DOI: 10.1161/circresaha.109.206581
|View full text |Cite
|
Sign up to set email alerts
|

TRPC1 Channels Are Critical for Hypertrophic Signaling in the Heart

Abstract: Rationale: Cardiac muscle adapts to increase workload by altering cardiomyocyte size and function resulting in cardiac hypertrophy. G protein-coupled receptor signaling is known to govern the hypertrophic response through the regulation of ion channel activity and downstream signaling in failing cardiomyocytes. Objective: Transient receptor potential canonical (TRPC) channels are G protein-coupled receptor operated channels previously implicated in cardiac hypertrophy. Our objective of this study is to better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
156
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(168 citation statements)
references
References 41 publications
11
156
1
Order By: Relevance
“…Moreover, Trpc1 −/− mice were shown to develop less cardiac hypertrophy in response to 8 weeks of pressure-overload stimulation or 4 weeks of AngII infusion (10). Although our study is in agreement, we identified several concepts that further establish an overarching Ca 2+ regulatory paradigm in the heart.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Moreover, Trpc1 −/− mice were shown to develop less cardiac hypertrophy in response to 8 weeks of pressure-overload stimulation or 4 weeks of AngII infusion (10). Although our study is in agreement, we identified several concepts that further establish an overarching Ca 2+ regulatory paradigm in the heart.…”
Section: Discussionsupporting
confidence: 68%
“…More recently, some data have emerged suggesting that TRPC channels are required for cardiac hypertrophy, because Trpc1 −/− mice and use of the TRPC3 inhibitory compound Pyr3 showed reduced pressure-overload growth (10,11). However, it remains unknown whether endogenous TRPC channels and associated Ca 2+ influx are altered in pathologic cardiac hypertrophy and which subfamily might be required for pathologic growth.…”
mentioning
confidence: 99%
“…Based on our observation that a single point mutation within the TRPC3 pore causes specific elimination of Ca 2+ permeation, we set out to use this genetically engineered cation channel to explore the cellular impact of the TRPC3-mediated monovalent conductance and to identify downstream signaling pathways that are specifically linked to either the monovalent transport or to Ca 2+ entry through the channel pore. Because the TRPC monovalent conductance is considered of particular importance in excitable cells, and because recent studies have demonstrated the relevance of TRPC channels in cardiac pathophysiology (2,4,7,18) we focused on the cardiac system, using the HL-1 murine atrial cell line. Initially, we compared basic properties of TRPC3 signaling in HL-1 cells with those in the well characterized electrically nonexcitable HEK293 system.…”
Section: Resultsmentioning
confidence: 99%
“…Cardiac-specific expression of dn-TRPC3, dn-TRPC4, or dn-TRPC6 each antagonized the degree of cardiac hypertrophy after pressure overload stimulation or infusion of phenylephrine/angiotensin II (148). Similarly, mice deficient in Trpc1 showed reduced cardiac hypertrophy and disease after pressure overload or neuroendocrine agonist stimulation (149). These results suggest that an appropriately designed inhibitor that blocks one or more of these TRPC channels might be an effective therapeutic for cardiac hypertrophy or the transition to heart failure.…”
Section: Manipulation Of Ca 2+ Dependent Signaling Effectorsmentioning
confidence: 96%